Epidemiological Study of Uveal Melanoma from US Surveillance, Epidemiology, and End Results Program (2010–2015) - Yufeng Xu; Lixia Lou; Yijie Wang; Qi Miao; Kai Jin; Menglu Chen; Juan Ye (Journal of Ophthalmology)
Purpose. Uveal melanoma is the most common intraocular malignancy, and the American Joint Committee on Cancer (AJCC) changed its staging methodology from 2010, incorporating notable changes into the T-staging. There were few literatures evaluating the epidemiological trend and risk factors of survival in multicenter longitudinal studies regarding the new staging system. Methods. We performed population-based cohort analyses using the Surveillance, Epidemiology, and End Results (SEER) database to identify patients with primary uveal melanoma from 2010 to 2015. Patients and potential prognosis indicators were extracted from SEER 18. Incidence rates, incidence rates ratios (IRR), annual percent changes (APC) in rate, hazard ratios (HR), 5-year accumulative overall survival (OS), and disease-specific survival (DSS) were calculated. Results. A total of 2631 patients for incidence analysis and 1142 patients for survival analysis were retrieved. The overall incidence of uveal melanoma was 4.637 per million (95% confidence interval (CI), 4.458–4.821), which was significantly elevated by average APC of 4.215% (p=0.03). Females had significantly lower incidence (4.076 per million, IRR, 0.768, 95% CI, 0.710–0.832) with noticeable differences among age, race, origin, and laterality in sex-stratified analyses as well. Survival analyses revealed 5-year accumulative OS and DSS for patients with uveal melanoma of 61.8% and 66.5%, respectively. Age, AJCC stage, and radiation therapy were found to be consistent predictors in both univariate and multivariate analysis models. Conclusion. Incidence of uveal melanoma increased by significant APC and varied between genders. Determinants of survival included age at diagnosis, AJCC stage, and radiation therapy.